Ефективність використання запропонованого лікувально-профілатичного комплексу в дітей-інвалідів із захворюваннями тканин пародонта - Гавриленко, Марина Аркадіївна; Gavrilenko, M. A. (My University, 2017)
Діти-інваліди з хворобами центральної нервової системи, крові, органів дихання та з психічними розладами мають високий відсоток стоматологічних хвороб [1]. Захворювання тканин пародонта залишаються одними з найпоширеніших стоматологічних хвороб. Відома ціла низка сучасних публікацій про техніки і методи лікування запальних і деструктивних хвороб тканин пародонта [5-7]. Але їх виконання ускладнене в такої категорії пацієнтів як діти з інвалідністю з хворобами центральної нервової системи, системи крові, органів дихання і з психічними розладами, зважаючи на прояви й особливості основної хвороби. Тому важливим завданням є дотримання якісної гігієни порожнини рота і своєчасна профілактика стоматологічних хвороб у таких дітей. Children with disabilities who suffer form diseases of the Central nervous system, blood diseases, respiratory and mental disorders have a high percentage of dental diseases. We propose a set of preventive measures aimed to improve dental health in children with disabilities. It includes the sanitation of the oral cavity and conduction of hygienic cleaning of teeth, fissure sealing, fluoridation of teeth under general anesthesia, followed by administration of complex of drugs. Drugs were administered in conjunction with pediatricians and doctors taking care after the children with disabilities. Doses of drugs were administered according to age.The purpose of the study: to improve the quality of treatment and prevention of diseases of periodontal tissues in children-invalids with diseases of the central nervous system, blood system, respiratory and mental disorders. Materials and methods. Disabled children with central nervous system diseases, mental disorders, diseases of the blood system, respiratory organs, ones who suffer from chronic catarrhal gingivitis mild and moderate severity at the age from 2 to 15 years.
The effectiveness of theusage of medical-professional proposed complex for disabled children with the diseases of periodontal tissues
Keywords: children with disabilities; general anesthesia; prevention of dental diseases; periodontal tissues; hygienic cleaning of the teeth